2005
DOI: 10.1111/j.1478-3231.2005.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of protective action of bicyclol against CCl4‐induced liver injury in mice

Abstract: Bicyclol is a novel synthetic drug for the treatment of chronic viral hepatitis in China. This paper reports the protective action of bicyclol against experimental liver injury in mice and its mechanism of action. Oral administration of bicyclol markedly reduced the elevated serum transaminases (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)) and the hepatic morphologic changes induced by CCl(4) in mice. Mechanistic studies demonstrated that bicyclol significantly inhibited CCl(4)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 16 publications
1
33
0
2
Order By: Relevance
“…Bicyclol demonstrates effects on anti-liver injuries, anti-hepatitis B virus and anti-liver fibrosis in animal models with its clinical efficiency in treatment of chronic viral hepatitis, a tolerant and safety in long-term oral administration by preclinical toxicity studies. [3][4][5][6][7][8][9] Recently, the chemoprevention of Bicyclol against the preneoplastic lesions in rat liver induced by diethylnitrosamie (DEN) 10 is revealed (in the process of publication), consistent with the similar study of DDB for in vitro model. 11 Interestingly, as an intrinsic multiple drug resistant (MDR) model, 12 the DEN induced the expression of p-glycoprotein, the Mdr-1 gene product, in the rat hepatic preneoplastic lesions.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Bicyclol demonstrates effects on anti-liver injuries, anti-hepatitis B virus and anti-liver fibrosis in animal models with its clinical efficiency in treatment of chronic viral hepatitis, a tolerant and safety in long-term oral administration by preclinical toxicity studies. [3][4][5][6][7][8][9] Recently, the chemoprevention of Bicyclol against the preneoplastic lesions in rat liver induced by diethylnitrosamie (DEN) 10 is revealed (in the process of publication), consistent with the similar study of DDB for in vitro model. 11 Interestingly, as an intrinsic multiple drug resistant (MDR) model, 12 the DEN induced the expression of p-glycoprotein, the Mdr-1 gene product, in the rat hepatic preneoplastic lesions.…”
Section: Introductionsupporting
confidence: 64%
“…1A), developed from Chinese herb Fructus Schizandrae. [1][2][3] Bicyclol indicates the improvement of pharmacological efficiency and applies for the novel clinical actions with the structure reformed. Bicyclol demonstrates effects on anti-liver injuries, anti-hepatitis B virus and anti-liver fibrosis in animal models with its clinical efficiency in treatment of chronic viral hepatitis, a tolerant and safety in long-term oral administration by preclinical toxicity studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bicyclol is a liver-protective substance administered to patients with various types of liver disease. Its mechanism of action may be closely associated with free radical-scavenging properties, protection against lipid peroxidation, protection of hepatic cell membranes and mitochondrial function (12), and inhibition of inflammatory cytokines (13). It was demonstrated in experimental and clinical studies that Bicyclol decreased serum transaminase levels and resulted in improvements as observed by pathology (14)(15)(16).…”
Section: Introductionmentioning
confidence: 97%
“…For example, acute liver damage induced by carbon tetrachloride (Liu et al, 2005), acetaminophen (Hou et al, 2008), concanavalin A (Bao and Liu, 2009), and D-galactosamine (GalN)/lipopolysaccharide (LPS) can be ameliorated by bicyclol administration. Further studies demonstrated that bicyclol treatment resulted in hepatic activation of heat shock transcription factor 1 (HSF1), which stimulated heat shock protein (HSP) 27 and HSP70 expression Liu, 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%